Notch Signaling in Cardiovascular Disease and Calcification - Rusanescu, Gabriel; Weissleder, Ralph; Aikawa, Elena (Current Cardiology Reviews, 2008)
Recent increase in human lifespan has shifted the spectrum of aging-related disorders to an unprecedented upsurge in cardiovascular diseases, especially calcific aortic valve stenosis, which has an 80% risk of progression to heart failure and death. A current therapeutic option for calcified valves is surgical replacement, which provides only temporary relief. Recent progress in cardiovascular research has suggested that arterial and valve calcification are the result of an active process of osteogenic differentiation, induced by a pro-atherogenic inflammatory response. At molecular level, the calcification process is regulated by a network of signaling pathways, including Notch, Wnt and TGFbeta/BMP pathways, which control the master regulator of osteogenesis Cbfa1/Runx2. Genetic and in vitro studies have implicated Notch signaling in the regulation of macrophage activation and cardiovascular calcification. Individuals with inactivating Notch1 mutations have a high rate of cardiovascular disorders, including valve stenosis and calcification. This article reviews recent progress in the mechanism of cardiovascular calcification and discusses potential molecular mechanisms involved, focusing on Notch receptors. We propose a calcification model where extreme increases in vascular wall cell density due to inflammation-induced cell proliferation can trigger an osteogenic differentiation program mediated by Notch receptors.
Keywords: atherosclerosis